Predictors of radiographic outcomes of conservative and surgical treatment of Legg-Calvé-Perthes disease - Stančák, Andrej; Kautzner, Jakub; Chládek, Petr; Adamec, Ondřej; Havlas, Vojtěch; Trč, Tomáš (International orthopaedics, 2022)
PURPOSE: Treatment outcomes of conservative and surgical treatment of Legg-Calvé-Perthes disease (LCPD) have been shown to be conditioned by a number of factors that may vary across different populations. This retrospective study aimed to evaluate factors affecting radiographically assessed treatment outcomes in patients treated surgically or conservatively for LCPD at Faculty Hospital Motol, Prague, Czech Republic, between the years 2006 and 2019. METHODS: Data of forty-seven children comprising 52 hips were analysed. Treatment outcomes were evaluated according to Stulberg classification. Predictors included the initial stage of fragmentation of the hip joint according to Herring classification, type of treatment (conservative or surgical), age at the time of diagnosis and sex. RESULTS: Older age and severity of LCPD according to Herring classification but not the type of treatment were the strongest factors determining treatment outcomes. Treatment outcomes were comparable in patients treated conservatively or surgically both across the whole cohort of patients and a group of young children < six years of age. CONCLUSIONS: Results strengthen the roles of severity of the LCPD at onset of treatment and age of the patient in predicting treatment outcomes in patients with LCPD. Conservative and surgical treatments appear to yield similar treatment outcomes irrespective of age of patients.
Keywords: Perthesova nemoc; Child; Osteotomy; retrospektivní studie; lidé; kyčelní kloub; Hip Joint; osteotomie; dítě; předškolní dítě; Legg-Calve-Perthes Disease; Retrospective Studies; Treatment Outcome; Child, Preschool; výsledek terapie; Humans